2017
DOI: 10.1093/brain/aww322
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of convulsive seizure termination and postictal generalized EEG suppression

Abstract: It is not fully understood how seizures terminate and why some seizures are followed by a period of complete brain activity suppression, postictal generalized EEG suppression. This is clinically relevant as there is a potential association between postictal generalized EEG suppression, cardiorespiratory arrest and sudden death following a seizure. We combined human encephalographic seizure data with data of a computational model of seizures to elucidate the neuronal network dynamics underlying seizure terminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
45
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 45 publications
10
45
0
1
Order By: Relevance
“…7). Following the work of Bauer et al [40], we also used the data to obtain a gamma distribution fit which showed that short SED durations had a distribution with α > 1 (6.3, Confidence Interval: 5.3-7.4), which is consistent with the analysis done in [35] on the in vivo data. Long SED durations had a gamma distribution with (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…7). Following the work of Bauer et al [40], we also used the data to obtain a gamma distribution fit which showed that short SED durations had a distribution with α > 1 (6.3, Confidence Interval: 5.3-7.4), which is consistent with the analysis done in [35] on the in vivo data. Long SED durations had a gamma distribution with (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Mathematical modeling of postictal suppression suggests a deterministic process associated with longer interclonic intervals and reduced connectivity prior to seizure termination. 5 This agrees with the hypothesis that seizures follow a set pathway through brain states. 4,6 The postictal period is commonly characterized by a period of low energy that slowly returns to interictal norms (referred to here as postictal suppression).…”
Section: Introductionsupporting
confidence: 89%
“…Critical transition models assume that seizure onsets and offsets may not begin and end entirely as a result of random fluctuations in cortical activity or input, but rather that seizures follow a path that must be completed as the brain transitions to the interictal state. Mathematical modeling of postictal suppression suggests a deterministic process associated with longer interclonic intervals and reduced connectivity prior to seizure termination . This agrees with the hypothesis that seizures follow a set pathway through brain states…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations